Barbara Kingsolver's world : nature, art, and the twenty-first century - Wagner-Martin, Linda (New York, NY : Bloomsbury Academic, 2014)
"Since Barbara Kingsolver published The Bean Trees in 1988, her work has been of great interest to readers -- first, American readers; then British and South African readers; and finally to readers the world over. With incredible speed, Kingsolver became one of the best-known United States writers, a person who collected honors and awards as if she were a much more mature literary producer. From the beginning Kingsolver touched an elbow of keen interest in her readers: hers was the voice of world awareness, a conscientious voice that demanded attention for the narratives of the disadvantaged, the politically troubled, the humanly silenced. By paying special attention to her non-fiction (essays and books), this new study by renowned literary critic Linda Wagner-Martin highlights the way Kingsolver has become a kind of public intellectual, particularly in the twenty-first century. It will provides fresh readings of each of her novels, stories, and poems."--Provided by publisher
Flight Behavior: Dellarobia's bildungsroman -- The innocence of The Bean Trees -- Pigs in Heaven and its interrogation -- Animal Dreams, a prototypical ecological novel -- The fiction of Kingsolver's non-novels -- Kingsolver as essayist: a different expertise -- Kingsolver as poet -- The Poisonwood Bible as apex -- The prodigality of Prodigal Summer -- Traveling to Animal, Vegetable, Miracle: A Year of Food Life -- Small Wonder: staying alive and the Bellwether prizes -- The Lacuna -- Flight Behavior, our bildungsroman.
Includes bibliographical references (pages 199-212) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Kingsolver, Barbara -- Criticism and interpretation; Kingsolver, Barbara; Literary studies: general; Literary studies: fiction, novelists & prose writers; LITERARY CRITICISM -- American -- General; Criticism, interpretation, etc